Developing transferable skills - Denicolo, Pam; Reeves, Julie
If you're a doctoral and early career researcher seeking a succinct guide to developing transferable skills, or are responsible for developing the transferable skills of others, this book takes you through everything you need to know. In the UK, possession of a doctorate is no longer the rarity it once was and the competitive economic climate makes it even more critical that you can convince prospective employers of both your specialist and generic skills. The authors take you through why transferable skills are needed, and how they can be acquired, evidenced and marketed. With coverage of project management, team working, communication, leadership and technical skills, this book is an essential guide for any researchers who want to make the most of the skills you have and acquire the skills you need.
What are transferable skills and why they are needed? -- How can researchers identify which transferable skills are needed? -- How can transferable skills be acquired? -- What are the key intellectual skills directly related to research? -- What skills are involved in dealing with information and with maintaining integrity as a researcher? -- What are the key practical research project skills? -- What are the key people skills and personal attributes? -- How can skill development be evidenced, assessed and evaluated? -- How can transferable skills be marketed effectively to enhance employability? (Dawn Duke) -- How can researchers make a successful transition to another employment? -- How can transferable skills become an integral part of life?
Keywords: Vocational qualifications; Doctoral students; Career development; Employability; Careers